1994
DOI: 10.1073/pnas.91.8.3289
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cardiac Na+ channels expressed in a mammalian cell line and in ventricular myocytes by protein kinase C.

Abstract: Cardiac rH1 Na+ channel a subunits were expressed in cells of the Chinese hamster lung 1610 cell line by transfection, and a stable cell line exprsing cardiac Na+ channels (SNa-rHl) was isolated. Mean Na+ currents of 2.2 ± 1.0 nA were recorded, which corresponds to a cell surface density of approximately 1-2 channels active at the peak of the Na+ current per pam2. The expressed cardiac Na+ current was tetrodotoxin resistant (Kd = 1.8 FM) and had voltagedependent properties similar to those of the Na+ current i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
73
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 25 publications
12
73
0
Order By: Relevance
“…Similarly, we found that application of 0.5 μM Ro-31-8425 application blocked an increase in Nav1.8 currents induced by either 8-Br-cAMP or the cAMP analogue forskolin [23]. This was supported by the fact that application of a PKC inhibitor (staurosporine or PKC [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ) caused a marked inhibition of the forskolin-induced increase in the G V1/2 base (i.e. the percentage change in G at baseline V 1/2 ) [24,36,46].…”
Section: Modulation Of Nav18 Currents By Pkcsupporting
confidence: 67%
See 2 more Smart Citations
“…Similarly, we found that application of 0.5 μM Ro-31-8425 application blocked an increase in Nav1.8 currents induced by either 8-Br-cAMP or the cAMP analogue forskolin [23]. This was supported by the fact that application of a PKC inhibitor (staurosporine or PKC [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ) caused a marked inhibition of the forskolin-induced increase in the G V1/2 base (i.e. the percentage change in G at baseline V 1/2 ) [24,36,46].…”
Section: Modulation Of Nav18 Currents By Pkcsupporting
confidence: 67%
“…The application of the PKC inhibitor PKC [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] significantly suppresses the forskolin-induced increase in the Nav1.8 current but the PKA inhibitor WIPTIDE has no significant effect on the PKC activator phorbol12, 13-dibutyrate (PDBu)-induced increase in the current [36]. When considering these results together, it is possible that PKCinduced phosphorylation of the channel protein at serine 1506 is required to enable PKA-induced phosphorylation of other sites on the channel protein suggested by Li et al [40] in a relationship between PKC and PKA on the convergent regulation of Na + channels.…”
Section: Interaction Between Pkc and Pka On Nav 18 Currentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study clearly shows that co-expression of FHF1B produces a significant hyperpolarizing shift of the voltage dependence of inactivation of Na v 1.5. This shift is similar to that attributed to the phosphorylation of Ser 1505 in the cytoplasmic linker joining domains 3 and 4 by protein kinase C (48,49). Other residues, for example Ser 526 and Ser 529 in the cytoplasmic loop linking domains 1 and 2 (L1) of Na v 1.5, have been reported to be phosphorylated by cAMP-dependent protein kinase (50).…”
Section: Discussionsupporting
confidence: 57%
“…In turn, this lowers the amount of the oxidized form of glutathione and increases the reduced form. Thus, this shift of cellular redox state might finally alter important cardiac ion currents like transients I to (Rozanski and Xu 2002), I Ca,L (Hool 2008) or I Na (Qu et al 1994). However, these theoretical considerations have to be confirmed in vivo, not only as Wagner et al (2008) provided evidence that the activation of the MR per se depends on the intracellular redox state of cardiac myocytes.…”
Section: Effects Of the Modulation Of Oxidative Stress By Aldosteronementioning
confidence: 99%